PENGARUH KOMITMEN ORGANISASIONAL, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA MANAJERIAL PADA RUMAH SAKIT SWASTA DI KOTA PEKENBARU - Laura Amelya Br Napitupulu; Rita Anugerah Mafis; Mudrika alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the influence of organizational commitment, motivation and competence to managerial performance at a private hospital in the city of pekanbaru. This study was conducted at 18 private hospital in the city of pekanbaru. The sampling method used in this study is purposive sampling method. The respondent in this study is division manager/functional, the head of division/section/sub section. The sample used in this study is 70 respondent selected by using purposive sampling method. The independent variable is organizational commitment, motivation and competence. The dependent variable is the performance of managerial. The hypotheses then tested is multiple linearregression analysis by using SPSS version 20.0. The result of this study indicated that the organizational commitment did not significant effect on managerial performance with level significant 0,775 >0,05, the motivation of significantinfluence on managerial performance with level significant 0,001<0,05, while the competence of significant influence on managerial performance with level significant 0,000<0,05. The result ajusted R-Square of the test show independentvariables to dependent variables is 89%. While the rest 11% influenced by other variables not examined in this study.Keyword: Organizational Commitment, Motivation, Competence, ManagerialPerformance